Porcine Choroid Plexus Epithelial Cells Induce Streptococcus suis Bacteriostasis In Vitro - Adam, Rüdiger A. (American Society for Microbiology, 2004)
The involvement of the choroid plexus in host defense during bacterial meningitis is unclear. Aiming to elucidate possible antibacterial mechanisms, we stimulated primary porcine choroid plexus epithelial cells (pCPEC) with proinflammatory cytokines and challenged them with various Streptococcus suis strains. In the supernatant of gamma interferon (IFN-γ)-stimulated pCPEC, streptococcal growth was markedly suppressed. Costimulation with tumor necrosis factor alpha enhanced this bacteriostatic effect, while supplementation of l-tryptophan completely eliminated it. We also demonstrate that an activation of indoleamine 2,3-dioxygenase in the pCPEC seems to be responsible for the IFN-γ-induced bacteriostasis. This supports the hypothesis of an active role of the choroid plexus in host defense against bacterial meningitis.